Barge NOME CITY damaging the North American Transportation & Trading Co.'s wharf during a storm, Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Barge "Nome City" smashing the N.A.T. & T. Co.'s wharf, Nome" Original image in Hegg Album 38, page 11. Original photograph by Eric A. Hegg 1459; copied by Webster and Stevens 212.A